COMMODIFICATION OF SPACES AT BALANGAN BEACH IN THE PRE WEDDING PHOTO PHENOMENON IN BALI - Surya Dinata, Ramanda Dimas; Sinar Wijaya, I Putu (International Conference on Cultural Studies, 2019)
The problems faced in the last seven years is how some public places in Bali, one of that is Balangan beach area of Badung Bali has happened commodification practice space since the existence of photo pre wedding phenomenon. How the natural space in the area is commercialized and raises complex problems in it. The purpose of this article is to know more deeply what causes the practice of commodification in the Balangan beach area and the impact of any commodity practices. Sources of data obtained through qualitative methods include observation and interviews, and analyze it by using critical theory such as commodity theory covers the production, distribution, and consumption, and then linked with the concept of human ecology. Based on the results of the analysis, the practice of commodification in the phenomenon of photo pre wedding in Bali, especially in the area of Balangan occurs because influenced by several factors, among others, the community considers pre wedding photos as something exclusive, and worth the additional cost, employment backgrounds of local people who are still in category lower middle and region that mostly controlled by foreign investors caused the economic gap between outsiders and insiders in commodification area of Balangan beach. The problems are not only marginalized communities, especially communities around the region also poorly managed systems include the management of informal and controlled by foreign investors.